TINJAUAN KETERLAMBATAN PENGEMBALIAN REKAM MEDIS PASIEN PASCA RAWAT INAP DI RUMAH SAKIT SALAK BOGOR - Rindiani Junianti; Dina Sonia (Bajang Institute, 2021)
The implementation of medical records has a very broad scope of cooperation between work units, starting from hospital leaders, doctors, nurses to other health workers. One of the units involved in recording patient medical records is the Inpatient Unit. This study aims to determine the timeliness of returning inpatient medical record files to the medical record unit and the delay factor in returning inpatient medical records. This research was conducted on April 26 – June 26, 2021 descriptively with a qualitative approach with data collection methods using observations, interviews, and documentation studies. The results were obtained in the May – June period from a total of 751 inpatient medical record files that returned on time to the medical record unit as many as 594 files (61%) and 157 files (39%). The factor of delay in returning inpatient medical records is that there are still some nurse officers who do not follow the applicable SOP rules in returning inpatient files, namely 2x24 hours after the patient returns, the lack of special care personnel for the management of inpatient medical records and incomplete filling of the record form. medical treatment by doctors and room nurses. So the researcher gives suggestions to be further improved in the timeliness of returning inpatient medical record files so that there is no delay in returning inpatient medical record files to the medical record unit.